EFFECT OF BUDGETARY PARTICIPATION ON BUDGETARY SLACK WITH MODERATION VARIABLES ARE ORGANIZATIONAL CULTURE, ENVIRONMENTAL UNCERTAINTY AND INFORMATIONASYMMETRY - Rizqi, Reza Muhammad (Jurnal Ekonomi dan Bisnis Indonesia, 2018)
ABSTRACT The problems of this research is occurred in previous studies on the influence of budgetary participation on budgetary slack and high budgetary slack happened at Hospital of Sumbawa Besar become the motivation in this research. Data collection was done through the distribution of questionnaires to the responden,from 48 questionnaires, only 45 questionnaires could be used. This study used a model based on the SEM variant of SmartPLS. The research instrument has passed the validity and reliability test. The results showed that budgetary participation have effect on budgetary slack. This study may identification the interaction between budgetary participation and organizational culture has a positive and significant effect on budgetary slack, environmental uncertainty has a negative and significant effect, and information asymmetry has a negative and significant effect between budgetary participation and budgetary slack. The implications of this study are expected to be useful for the hospital and the government so that it can be a guide in preparing and setting a more effective and efficient budget, so that the goals of the organization can be easily achieved. Keywords: Budgetary Participation, Organizational Culture, Environmental Uncertainty, Information Asymmetry, Budgetary Slack.